THE EFFECT OF ANTLIONS EXTRACT TOWARDS BLOOD GLUCOSE LEVEL OF MALE SWISS MICE INDUCED BY STREPTOZOTOCIN - Rizky Indra Puspito; Santoso Jaeri; Y.L Aryoko Widodo; Andrew Johan (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
ABSTRACTBackground: Diabetes mellitus is a disease that is included in the group of metabolic diseases, characterized by hyperglycemia that occurs due to abnormal insulin secretion. Generally, treatment of diabetes mellitus uses insulin injection and Oral Hypoglycemic Drugs (OHD). In addition there are also animals are trusted by public in healing diabetes mellitus. Antlions (Myrmeleon sp) is a useful animal to treat diabetes mellitus. The body of antlions contains sulfonylureas which is a substance that stimulates insulin secretion in pancreatic beta cells. Aim: The objective of this research was to analyze the effect of antlions extract on blood glucose level of male swiss mice induced by streptozotocin Methods: This research was a pure experimental laboratory study and the design used is the Pre Test and Post Test Control Group Design, which is done by comparing the results of observations in the control and treatment groups after the action was done. Sampling was done using the simple random sampling technique. The sample size used in this study amounted to 30 mice. The data obtained were analyzed using ANOVA test with a confidence level of 95%. Results: The administration of antlions extract could lower (p<0.05) blood glucose levels in male Swiss mice after 28 days of treatment. The administration of antlions extract with doses of 14 mg/kgBW and 56 mg/kgBW significantly lowered blood glucose levels in male Swiss mice as evidenced by p=<0.001 and p=0.034. Whereas the administration of antlions extract with a dose of 28 mg/kgBW was less significant in lowering blood glucose levels in male Swiss mice (p=0.210). Conclusion: The administration of antlions extract (Myrmeleon sp.) with a dose of 14 mg/kgBW had the best effect on lowering blood glucose levels in male Swiss mice after 28 days of treatment. Keywords: diabetes mellitus, blood glucose, antlions